Irisin alleviated the reproductive endocrinal disorders of PCOS mice accompanied by changes in gut microbiota and metabolomic characteristics - Yang, Meina; Deng, Hongxia; Zhou, Siyu; Lu, Danhua; Shen, Xiaoyang; Huang, Lu; Chen, Yan; Xu, Liangzhi (Frontiers in Microbiology, 2024)
Introduction Folliculogenesis and oligo/anovulation are common pathophysiological characteristics in polycystic ovary syndrome (PCOS) patients, and it is also accompanied by gut microbiota dysbiosis. It is known that physical activity has beneficial effects on improving metabolism and promoting ovulation and menstrual cycle disorder in PCOS patients, and it can also modulate the gastrointestinal microbiota in human beings. However, the mechanism remains vague. Irisin, a novel myokine, plays a positive role in the mediating effects of physical activity. Methods Mice were randomly divided into the control group, PCOS group and PCOS+irisin group. PCOS model was induced by dehydroepiandrosterone (DHEA) and high-fat diet (HFD). The PCOS+irisin group was given irisin 400μg/kg intraperitoneal injection every other day for 21 days. The serum sex hormones were measured by radioimmunoassay. Hematoxylin and Eosin (H&E) Staining and immunohistochemistry (IHC) were conducted on ovarian tissue. The feces microbiota and metabolomic characteristics were collected by 16S rRNA gene sequencing and liquid chromatography-mass spectrometry (LC–MS). Results In this study, we demonstrated that irisin supplementation alleviated reproductive endocrine disorders of PCOS mice, including estrous cycle disturbance, ovarian polycystic degeneration, and hyperandrogenemia. Irisin also improved the PCOS follicles dysplasia and ovulation disorders, while it had no significant effect on the quality of oocytes. Moreover, irisin could mitigate the decreased bacteria of Odoribacter and the increased bacteria of Eisenbergiella and Dubosiella in PCOS mice model. Moreover, irisin could alleviate the increased fecal metabolites: Methallenestril and PS (22:5(4Z,7Z,10Z,13Z,16Z)/ LTE4). Conclusion These results suggest that irisin may alleviate the status of PCOS mice model by modulating androgen-induced gut microbiota dysbiosis and fecal metabolites. Hence, our study provided evidence that irisin may be considered as a promising strategy for the treatment of PCOS.